2003
DOI: 10.1159/000073340
|View full text |Cite
|
Sign up to set email alerts
|

Factors Enhancing Intestinal Adaptation after Bowel Compensation

Abstract: Intestinal failure (IF) refers to the condition in which certain causes lead to derangements in nutrient absorption capacity. Gut adaptation occurs in response to IF and it is both morphologic and physiologic in nature and can be mediated by growth factors and nutrients. Our paper reviews certain trophic growth factors that have important interactions relevant for intestinal growth, function and adaptation. Data Source: The literature was reviewed (data from both animal and human studies) and certain trophic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 92 publications
0
6
0
2
Order By: Relevance
“…To improve gut mucosal integrity after a thermal injury, a possible approach is to counter increased apoptosis by either decreasing the rate of programmed cell death or increasing small bowel epithelial cell proliferation. Several in vitro studies have shown that growth factors are crucial for the cell cycle and the proliferationdifferentiation-apoptosis pathway [7][8][9]. We therefore hypothesized that rhGH modulates small bowel mucosal cell proliferation and/or apoptosis and improves small bowel homeostasis after a thermal injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To improve gut mucosal integrity after a thermal injury, a possible approach is to counter increased apoptosis by either decreasing the rate of programmed cell death or increasing small bowel epithelial cell proliferation. Several in vitro studies have shown that growth factors are crucial for the cell cycle and the proliferationdifferentiation-apoptosis pathway [7][8][9]. We therefore hypothesized that rhGH modulates small bowel mucosal cell proliferation and/or apoptosis and improves small bowel homeostasis after a thermal injury.…”
Section: Discussionmentioning
confidence: 98%
“…The possible approach would encompass either to decrease the rate of apoptosis or to increase the rate of proliferation. Growth factors, such as recombinant human growth hormone (rhGH), are known to affect either apoptosis or proliferation in different organs, leading us to determine the effects of rhGH on small bowel epithelial cell homeostasis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of different hormones have been implicated in regulating gut growth including insulin-like growth factor-1, growth hormone, keratinocyte growth factor, and epidermal growth factor. 5 More recently, interest has focused on the actions of the intestinal hormone glucagonlike peptide-2 (GLP-2) not only because of its potent intestinotropic effects, but also because of the pleiotropic effects of GLP-2 on nutrient absorption, gut permeability, and mucosal cytoprotection. 6,7 GLP-2 is a 33 amino-acid peptide secreted by the enteroendocrine L cell of the intestinal epithelium.…”
mentioning
confidence: 99%
“…These include partial enterectomy, increased feeding, stimulation of autonomic nerves, and administration of neurotransmitters, thyroxin, growth hormone, corticosteroids, testosterone, gastrin, glucagon, glucagon-like peptide 2 and epidermal growth factor. 456,568,569 Key determinants of feeding-induced intestinal adaptation appear to be non-specific luminal stimulation, functional workload induced by polymeric nutrients, stimulation of pancreatic or biliary secretion as well as diverse humoral mediators and induction of intestinal hyperemia. 570 In the short bowel syndrome which occurs when there is insufficient length of the small intestine to maintain adequate nutrition following surgical resection of the intestine, the extent of adaptation depends on the anatomy of the resected bowel and the amount of bowel remaining.…”
Section: Hypertrophy and Hyperplasiamentioning
confidence: 99%